2010
DOI: 10.1002/pam.20507
|View full text |Cite
|
Sign up to set email alerts
|

Does supported employment work?

Abstract: Providing employment-related services, including supported employment through job coaches, has been a priority in federal policy since the enactment of the Developmental Disabilities Assistance and Bill of Rights Act in 1984. We take advantage of a unique panel data set of all clients served by the SC Department of Disabilities and Special Needs between 1999 and 2005 to investigate whether job coaching leads to stable employment in community settings. The data contain information on individual characteristics,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 15 publications
0
5
0
1
Order By: Relevance
“…Lower emotional and/or behavioural problems have been associated with the employment status of people with intellectual disabilities (Martorell, Gutierrez-Recacha, Pereda, & Ayuso-Mateos, 2008;McDermott, Martin, & Butkus, 1999;McInnes, Ozturk, McDermott, & Mann, 2010;Siperstein et al, 2014), as have absence of psychiatric symptoms (Martorell et al, 2008) and having fewer health problems (McDermott et al, 1999). Whilst some studies have found no association between health and/or mental health and employment outcomes (Faubion & Andrew, 2000;Moore, Feist-Price, & Alston, 2002;White & Weiner, 2004), in two of these studies receipt of employment-related services or training predicted employment (Moore et al, 2002;White & Weiner, 2004), suggesting that health-related barriers to obtaining employment may be addressed through appropriate service provision or training.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lower emotional and/or behavioural problems have been associated with the employment status of people with intellectual disabilities (Martorell, Gutierrez-Recacha, Pereda, & Ayuso-Mateos, 2008;McDermott, Martin, & Butkus, 1999;McInnes, Ozturk, McDermott, & Mann, 2010;Siperstein et al, 2014), as have absence of psychiatric symptoms (Martorell et al, 2008) and having fewer health problems (McDermott et al, 1999). Whilst some studies have found no association between health and/or mental health and employment outcomes (Faubion & Andrew, 2000;Moore, Feist-Price, & Alston, 2002;White & Weiner, 2004), in two of these studies receipt of employment-related services or training predicted employment (Moore et al, 2002;White & Weiner, 2004), suggesting that health-related barriers to obtaining employment may be addressed through appropriate service provision or training.…”
Section: Discussionmentioning
confidence: 99%
“…Lower emotional and/or behavioural problems have been associated with the employment status of people with intellectual disabilities (Martorell, Gutierrez-Recacha, Pereda, & Ayuso-Mateos, 2008;McDermott, Martin, & Butkus, 1999;McInnes, Ozturk, McDermott, & Mann, 2010;Siperstein et al, 2014), as have absence of psychiatric symptoms (Martorell et al, 2008) The majority of the studies in this review are cross-sectional, and as such, it is not possible to attribute causality. Even in the best-quality longitudinal study identified, the authors note that they cannot confirm the direction of the relationship between change in behaviour and day occupation .…”
Section: Discussionmentioning
confidence: 99%
“…As an additional component of follow-along and retention support, participants' positive or negative appraisals of job coaches are critical for graduates' successful adjustment and retention at work (Cheng et al, 2018;McInnes et al, 2010;Parsons et al, 2001). Despite the importance of job coach support, especially during the initial period of employment, job coaches rarely receive meaningful training or support for providing vocational skills instructions and effective support to students with disabilities (Gilson et al, 2021;Rogan & Held, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…This was true when looking at the supports scale overall, and also the subscales of the supports scale independently (i.e., personal supports and environmental supports). Specific perceived individual supports such as self-efficacy (Guay, Ratelle, Senecal, Larose, & Deschenes, 2006), education, job training (Kalil, Schweingruber, & Seefeldt, 2001), positive health (Edin & Lein, 2007), rehabilitation services such as benefits counseling (Tremblay, Smith, Xie, & Drake, 2006) and supported employment (Kregel, 2007;McInnes, Ozturk, McDermot, & Mann, 2010), managed stress, and psychiatric stability (Kalil et al, 2001) were hypothesized to be lower in rural areas, due numerous previous literature that references lack of education, job training opportunities (United States Department of Agriculture, 2015), and increased rates of individuals with disability/ies with little access to services (Reichart, Greiman & Myers, 2014) in rural areas. While past literature references such supports to be lower in rural areas, counselors in this sample did not perceive this in their responses.…”
Section: Discussionmentioning
confidence: 99%